2022
DOI: 10.3390/rs14051113
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Spectral Index for Automatic Canola Mapping by Using Sentinel-2 Imagery

Abstract: Because canola is a major oilseed crop, accurately determining its planting areas is crucial for ensuring food security and achieving UN 2030 sustainable development goals. However, when canola is extracted using remote-sensing data, winter wheat causes serious interference because it has a similar growth cycle and spectral reflectance characteristics. This interference seriously limits the classification accuracy of canola, especially in mixed planting areas. Here, a novel canola flower index (CFI) is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…We used the ground truth data described in Section 2.3 as a validation sample to assess the accuracy of rapeseed mapping. For the validation sample, we followed the non-proportional sampling allocation suggested by Olofsson et al [28] to increase the confidence in the accuracy assessment. The performance of the rapeseed mapping method was validated using the confusion matrix accuracy validation method and the F1 score.…”
Section: Accuracy Assessment Of Rapeseed Mappingmentioning
confidence: 99%
“…We used the ground truth data described in Section 2.3 as a validation sample to assess the accuracy of rapeseed mapping. For the validation sample, we followed the non-proportional sampling allocation suggested by Olofsson et al [28] to increase the confidence in the accuracy assessment. The performance of the rapeseed mapping method was validated using the confusion matrix accuracy validation method and the F1 score.…”
Section: Accuracy Assessment Of Rapeseed Mappingmentioning
confidence: 99%
“…In this paper, it was found that the accuracy of high-resolution LC datasets is better than low-resolution datasets. High-resolution image data can finely distinguish spectral features among ground objects, and more fine-scale information can be obtained [61]. Accordingly, high-resolution datasets are more advantageous than low-resolution datasets.…”
Section: Suggestions For Future Global Land Cover Mappingmentioning
confidence: 99%
“…Details of the bands used in this study can be found in Table 2. All bands were atmospherically corrected using the Sen2Cor processor tool, and the bands at 20 m resolution were rescaled to 10 m before being stacked [18,42]. In order to quickly and effectively select the optimal VIs suitable for winter wheat yield estimation and their importance ranking from the VI candidates, the RReliefF algorithm [43], as an extended variant of Relief [44], was adopted to screen the optimal VIs with high efficiency.…”
Section: Sentinel-2 Image Processingmentioning
confidence: 99%